Mechanistic Insights into the Cobalt-Mediated Radical Polymerization (CMRP) of Vinyl Acetate with Cobalt(III) Adducts as Initiators - Debuigne, Antoine; Champouret, Yohan; Jérôme, Robert; Poli, Rinaldo; Detrembleur, Christophe (Chemistry : a European journal, 2008)
Over the past few years, cobalt‐mediated radical polymerization (CMRP) has proved efficient in controlling the radical polymerization of very reactive monomers, such as vinyl acetate (VAc). However, the reason for this success and the intimate mechanism remained basically speculative. Herein, two mechanisms are shown to coexist: the reversible termination of the growing poly(vinyl acetate) chains by the Co(acac)2 complex (acac: acetylacetonato), and a degenerative chain‐transfer process. The importance of one contribution over the other strongly depends on the polymerization conditions, including complexation of cobalt by ligands, such as water and pyridine. This significant progress in the CMRP mechanism relies on the isolation and characterization of the very first cobalt adducts formed in the polymerization medium and their use as CMRP initiators. The structure proposed for these adducts was supported by DFT calculations. Beyond the control of the VAc polymerization, which is the best ever achieved by CMRP, extension to other monomers and substantial progress in macromolecular engineering are now realistic forecasts. A radical change! Some cobalt complexes mediate the radical polymerization of vinyl monomers, and particularly the one of vinyl acetate. Polymers with well‐defined and predictable molecular parameters can thus be prepared by the so‐called Cobalt‐Mediated Radical Polymerization (CMRP) system. The synthesis and the use of cobalt(III) adduct (see graphic) as CMRP initiator revealed the intimate mechanism of this technique, as supported by kinetics data and DFT calculations.